Discrete event simulation applying lean methodologies: case study. Wooden sector (2019)
In productive processes where parts are assembled, the assembly time is one of the most important problems that should be solved. Due to this, a case study was carried out in one company in the wooden sector, in which the Lean methodologies and the Discrete Events Simulation are integrated, to evaluate and improve the assembly processes of four-input wooden stowage. This study began by validating the process, then it was simulated in the Arena software, where great variability is observed in the assembly time of the four-input pallets, obtaining an average result of 25+/- 2 minutes. Due to this reason, the use of this methodology was proposed, applying the DMAIC cycle and carrying out controls in the process, it was possible to reduce it to 19 +/- 1 minute per stowage unit assembled, which meant a 24% reduction in the time spent manufacturing. All of this positively influenced the final delivery time of the product, so, with this new time, the company could satisfy the demand of its customers, and will be able to place its product on the market in less time.